2020
DOI: 10.3390/ijerph17134829
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Microbes from Street Fruit Drinks and Hygiene Behavior of the Vendors in Delhi, India

Abstract: Microbial contamination of fruit juices has caused major outbreaks, leading to significant morbidity and mortality in developing countries. The inept hygiene and safety practices followed by the juice vendors are the leading risk factors of the microbial contamination of juices. In this pilot study, the five most crowded markets in urban Delhi, including Kamla Nagar, University of Delhi (north campus), Tilak Nagar, Chandni Chowk, and Rohini, were selected for a questionnaire survey on the fruit juice v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
2
9
1
Order By: Relevance
“…Among all antibiotics tested against bacterial species, E. coli isolates were found to have 10 (91%) and 9 (82%) resistance against ciprofloxacin and streptomycin, respectively. This was contrary to the finding of Sharma et al 28 , who reported lower resistance of E. coli isolated from Street Fruit Drinks made from avocado in Delhi, India, against ciprofloxacin. However, Kechero et al 13 also reported higher sensitivity of E. coli isolated in commonly consumed fruit juices and vegetable salads made from avocado sold in some fruit juice houses in Addis Ababa, Ethiopia, against ciprofloxacin.…”
Section: Sample Codecontrasting
confidence: 99%
“…Among all antibiotics tested against bacterial species, E. coli isolates were found to have 10 (91%) and 9 (82%) resistance against ciprofloxacin and streptomycin, respectively. This was contrary to the finding of Sharma et al 28 , who reported lower resistance of E. coli isolated from Street Fruit Drinks made from avocado in Delhi, India, against ciprofloxacin. However, Kechero et al 13 also reported higher sensitivity of E. coli isolated in commonly consumed fruit juices and vegetable salads made from avocado sold in some fruit juice houses in Addis Ababa, Ethiopia, against ciprofloxacin.…”
Section: Sample Codecontrasting
confidence: 99%
“…The corresponding result was also observed in Delhi where Escherichia coli, Salmonella spp., Vibrio spp. isolated from different fruit juices exhibited a relatively higher resistance to ampicillin [40]. Apart from the Indian subcontinent, the outcome of this review is upheld by different studies conducted in Africa as well.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, it can be a reason for the presence of antibiotic resistant bacteria in street foods. Also, cross contamination can occur through water sources as street vendors frequently use municipal water for preparing fruit and for washing purposes [40]. Escherichia coli isolated from tap water collected from Dhaka, Jamalpur, Tangail, Netrokona, Kishoreganj showed resistance against tetracycline, erythromycin, amoxicillin, streptomycin and some other antibiotics [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Freshly prepared fruit juice as being considered healthy, may not be the case in some instances due to contamination by microbes [2]. Commonly found microorganisms in street juice include, Pseudomonas spp., Staphylococcus spp., Vibrio cholerae, Escherichia coli, Salmonella Typhi [3]. Factors that may contribute to microbial contamination of fruits juice ranges from contamination of fruits from the farm, handling, processing, packaging, and transportation, [4].…”
Section: Introductionmentioning
confidence: 99%